Clinical trial of tooth desensitization prior to in‐office bleaching. (6th July 2013) - Mehta, Deepak; Venkata, Suresh; Naganath, Meena; LingaReddy, Usha; Ishihata, Hiroshi; Finger, Werner J.
<x xml:space="preserve">Abstract</x> The aim of this clinical trial was to compare tooth sensitivity during and after bleaching with hydrogen peroxide gel following application of GLUMA Desensitizer PowerGel or placebo. Forty‐six subjects with sound maxillary incisors and canines were enrolled. Tooth shades were determined by comparison with a Vitapan Classic Shade guide. GLUMA Desensitizer PowerGel and placebo were randomly applied to the labial surfaces of the left or right anterior teeth for 1 min, which were then rinsed and dried. Then, Opalescence Boost PF 40% gel was applied onto labial enamel for 15 min. Sensitivity scores [recorded on a 10‐point visual‐analog scale (VAS)] were determined before, at 5, 10, and 15 min during, and 1, 24, 48 h and 1 wk after, the bleaching treatment. Shades were determined postbleaching and after 1 wk. Prebleaching application of GLUMA Desensitizer PowerGel significantly reduced tooth sensitivity during and after bleaching when compared with treatment with placebo. The whitening effects immediately and 1 wk after bleaching were significant when compared with the prebleaching shades. In conclusion, tooth pretreatment with GLUMA Desensitizer PowerGel for 1 min prior to 15 min of in‐office bleaching with 40% hydrogen peroxide gel was highly effective in reducing tooth sensitivity during and after bleaching.